Evaluation of BSP and DMP1 in hydroxyapatite crab shells used for dental socket preservation - Michael Josef Kridanto Kamadjaja; Sherman Salim; Wiwik Herawati Waluyo; Tengku Natasha Eleena binti Tengku Ahmad Noor (Dental Journal, 2023)
Background: Bone resorption due to tooth extraction leads to unpredictable bone volume for future prosthetics. Crab shells were promoted as a solution to prevent bone resorption, along with an effort to reduce biological waste. Purpose: This study aimed to analyze the expression of bone sialoprotein (BSP) and dentine matrix protein-1 (DMP1) in the wound healing process in tooth-extraction sockets after applying a crab shell-derived hydroxyapatite scaffold. Methods: The subjects (28 Cavia cobaya) were divided into control and treatment groups. The control group was left untreated, while the treatment group received a hydroxyapatite scaffold of Portunus pelagicus shell in the tooth socket. The expression of BSP and DMP1 was determined by immunohistochemical staining on days 7 and 14. One-way analysis of variance and Tukey’s honest significance difference test were used to find the groups with the most significant difference. Results: The highest mean expression of BSP and DMP1 was in the day 14 treatment group, while the lowest was in the day 7 control group. Conclusion: Administering hydroxyapatite scaffold derived from the Portunus pelagicus shell to the post-extraction sockets increased the expression of both BSP and DMP1.